2004
DOI: 10.1177/000312240406900207
|View full text |Cite
|
Sign up to set email alerts
|

Does Government Funding Suppress Nonprofits' Political Activity?

Abstract: A t least since de Tocqueville, autonomy from |the state has been considered a core feature of American civil society and a source of its many virtues. Recent historical and sociological research, however, shows that civil society and the state are deeply intertwined (Salamon 1995;Skocpol 1999;Smith and Lipsky 1993). Indeed, from some perspectives, it is more accurate to say that at least parts of civil society are dependent on the state rather than autonomous from it, prompting questions about the conse-quenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
244
0
8

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 226 publications
(262 citation statements)
references
References 24 publications
10
244
0
8
Order By: Relevance
“…Isomorphic pressures, it is argued, cause mission drift, loss of 'prophetic voice' and professionalization which leads to conformity and compliance. This 'limits alternative practices and aspirations and slowly transforms self-definition', which, in the longer term, decouples voluntary organisations from their civil society origins (Wolch 1990, Chaves et al 2004, DiMaggio and Powell 1983, Milbourne and Cushman 2015p. 467, Taylor 2011.…”
Section: Theoretical Framework: the Restructuring Of Welfare And Volumentioning
confidence: 99%
See 2 more Smart Citations
“…Isomorphic pressures, it is argued, cause mission drift, loss of 'prophetic voice' and professionalization which leads to conformity and compliance. This 'limits alternative practices and aspirations and slowly transforms self-definition', which, in the longer term, decouples voluntary organisations from their civil society origins (Wolch 1990, Chaves et al 2004, DiMaggio and Powell 1983, Milbourne and Cushman 2015p. 467, Taylor 2011.…”
Section: Theoretical Framework: the Restructuring Of Welfare And Volumentioning
confidence: 99%
“…Chaves et al (2004) concluded that state funding in the US had a positive impact on political advocacy and lobbying. They challenge neo-institutional, resource dependency perspectives concluding that 'nonprofit executives and board members .…”
Section: Theoretical Framework: the Restructuring Of Welfare And Volumentioning
confidence: 99%
See 1 more Smart Citation
“…However, due to its wider usage by scholars, this research opts to use the term: faith-based organizations throughout this study. Smith and Sosin considered an organization as religious or "faith-related" if it has a formal, administrative, or historical arrangement with a religious authority, or a specific mission that arises out of explicit religious values (Chaves, Stephens, & Galaskiewicz, 2014;Vanderwoerd, 2008). This study defines faith-based organization as an entity, independent of the government, which works towards improving the welfare and social development of particular communities.…”
Section: Definition Of Termsmentioning
confidence: 99%
“…The results from the research on government funding effects on advocacy are mixed (Chaves, Stephens, and Galaskiewicz 2004) or positive (Mosley 2011(Mosley ,2012) and depend to a great extent on how advocacy is defined in the model.…”
Section: Demand For Political/administrative Influencementioning
confidence: 99%